Comparative Analysis of Custard Produced from Selected Cereals (Guinea Corn, Maize, Rice and Millet) - Achimugu, Solomon; Okolo, Judith C.; Adaji, Patricia E. (Indonesian Food Science and Technology Journal, 2021)
This study looked at the proximate and organolleptic qualities of custard powder produced from four different cereals (guinea corn, maize, rice and millet). Proximate result ranged between 9.95-14.05%, 1.20-2.78%, 1.10-2.31%, 4.75-5.50%, 7.96-12.88% and 66.49-70.58% for moisture, ash, crude fiber, fat, protein and carbohydrate content respectively. There was significant difference in all the parameters evaluated. Product from guinea corn and Millet compared favourably with the product produced from the conventional cereal (maize). Also, sensory result revealed the preference of consumers for guinea corn and Millet based custard to the conventional primary raw material. The study established the superiority of custard from guinea corn and millet to that produced from maize. Keywords Custard, Maize, Guinea corn, Rice, Millet